Premature Consolidation of Regenerated Bone During Limb Lengthening with External Fixation in Achondroplastic Patients: Case Series and Literature Review - Edoardo Verme; Luca Bianco Prevot; Domenico Curci; Eleonora Caboni; Fabio Verdoni (Journal of Clinical Medicine, 2026)
Background: Premature consolidation of the regenerated bone is a relevant and underreported complication of limb lengthening in achondroplasia, with a reported incidence of 7–15% in the international literature. The gain-of-function fibroblast growth factor receptor 3 (FGFR3) mutation paradoxically enhances bone-healing capacity, predisposing patients to accelerated callus maturation during distraction osteogenesis and exposing patients to a risk of invasive procedures to treat this issue. This study reports the incidence and clinical features of premature consolidation in a cohort of achondroplastic patients treated with external fixation. Methods: A retrospective analysis was conducted on patients with achondroplasia who underwent lower limb lengthening (femur and/or tibia–fibula) between 2017 and 2024 at IRCCS Ospedale Galeazzi–Sant’Ambrogio (Milan, Italy). Inclusion criteria were ages 7–18 years, confirmed achondroplasia, and a clinical–radiological diagnosis of premature consolidation. Key parameters included the healing index (HI), length gained, proportional increase, and fixator duration. Results: Among 39 patients (112 segments: 46 femora and 66 tibia–fibula units), premature consolidation occurred in 7 patients (10 segments), yielding an overall incidence of 8.9%. The fibula was predominantly affected (6/10 segments). The mean HI was 33.47 days/cm for the tibia and 30.1 days/cm for the femur; the mean length gained was 8.1 cm and 8.2 cm, respectively. Conclusions: Premature consolidation affects approximately 9% of lengthened segments in achondroplastic patients, with a predilection for the fibula due to its passive indirect distraction mechanism. Early radiographic recognition and dynamic adjustment of the distraction protocol are essential to prevent surgical calloclasis and optimize outcomes, and further analyses of the FGFR3 mutation are fundamental to understand the biologic features of the bone during the lengthening and consolidation steps.